Strategic Responses to FDI in Emerging Markets: Are Core Members More Responsive than Peripheral Members of Business Groups? - Ayyagari, Meghana; Dau, Luis Alfonso; Spencer, Jennifer (Academy of Management Journal, 2015)
With increasing foreign direct investment (FDI) into emerging markets, local firms must make critical strategic decisions in order to remain competitive. When faced with multinational enterprises (MNEs) announcing FDI into their industry, local firms can expand operations and challenge the MNE head on, or refrain from responding directly, effectively ceding market share to the MNE investor. We propose that local firms’ responses are shaped by their affiliation with, and position in, a business group. Using data on investment announcements by MNEs and local firms in India from 1995 to 2010, we find that firms that are affiliated with business groups tend to be more sensitive to MNE investment announcements than are stand-alone firms. More professionally managed group affiliate firms are more likely to respond to MNE threats. Furthermore, firms that are in the group’s identity domain—that is, those holding more prominent positions within their group (especially as measured by centrality in the group’s directorship network)—appear more likely to respond to MNE investment announcements. Overall, our results highlight the importance of business group affiliation in examining FDI spillovers in emerging markets.